Efeitos da administração sistêmica do kombucha fermentado em chá verde na periodontite experimental em ratos - Silva, Everton Cavalcante da (2023)
The aim of this study was to evaluate the effects of administering Kombucha (KB)' fermented in green tea on the establishment and development of experimental periodontitis in rats. Sixty male Wistar rats (200-250 g) were distributed in two experimental sets with 5 groups (n=6): PE (submitted to experimental periodontitis); CV (treated with green tea); KB4, KB8 and KB12 (KB-treated with 4, 8 or 12 days of fermentation). The right hemimaxilla of the PE group was defined as the Control group (C). KB or green tea were administered daily (5 ml/kg) until the end of the experiment. On the 28th day of administration, the animals underwent experimental periodontitis induction by means of ligature. After euthanasia (39th day), hemimaxillas, kidneys, livers, intestines and blood were collected. Half of the hemimaxilla samples were dissected, stained with methylene blue, photographed and radiographed. The images obtained were exported and analyzed, where the variation in the area of alveolar bone loss (ΔPOA) and the variation in radiographic bone density (DRO) in the furcation region were evaluated. The other half was decalcified and processed for histopathological analysis along with the other structures. Blood was used for determination of hepatotoxicity markers. There was an increase in ΔPOA in the PE group when compared to the C group. The groups treated with green tea or KB had a lower ΔPOA compared to the PE group. Furthermore, only KB8 presented reduced ΔPOA in relation to CV. As for the shades of gray, a reduction in the DRO variation was observed in the CV and KB4 groups, when compared to PE. In the histomorphometric analysis, the CV, KB4, KB8 and KB12 groups showed a smaller area of bone loss and periodontal ligament when compared to the PE group. In the histopathological analysis, the CV and KB8 groups had higher bone destruction scores than the C group. CV and KB12 had higher scores for the presence of inflammatory infiltrate than the C group. Finally, the cementum destruction scores were higher in KB12, when compared to group C. Edema and hemorrhage scores in the hepatic sinusoids were higher in the PE and CV groups compared to the other groups. Furthermore, CV showed increased levels of hepatotoxicity markers when compared to the PE group. Groups that received KB showed a reduction in serum levels of these enzymes in relation to CV. Finally, when compared to the PE and CV groups, the groups treated with KB showed an increase in the amount of intestinal mucous cells in a manner dependent on the fermentation time. Therefore, it is concluded that both green tea and KB on different days of fermentation had an anti-resorptive effect on experimental periodontitis, in addition, KB did not induce liver or kidney changes, being associated with greater protection of the intestinal mucosa, in addition to present a therapeutic potential for the control of periodontitis.